2020
DOI: 10.1002/slct.201904962
|View full text |Cite
|
Sign up to set email alerts
|

12‐Tungstosilicic Acid H4[W12SiO40] Over Natural Bentonite as a Heterogeneous Catalyst for the Synthesis of 3,4‐dihydropyrimidin‐2(1H)‐Ones

Abstract: Regionally available bentonite was modified by using heteropolyacid 12‐tungstosilicic acid H4[W12SiO40] (TSA). The prepared 10–30 % TSA/bent catalysts were characterized by XRD, FTIR, FeSEM and EDS. The catalytic activity of all three samples was studied on classical Biginelli reaction. Among all, 30 % TSA/bent displayed high catalytic activity and reusability. The effect of solvent was also undertaken to find the best media for the reaction. This protocol was extended to various aldehydes for the synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 78 publications
(95 reference statements)
3
19
0
Order By: Relevance
“…The intensity of this peak decreased in all three samples and almost vanished in 30 % Fe(III)/bent. It showed that crystallinity of SiO 2 turned to amorphous nature [88,96,102] as similar observation made by us in our previous work [93,94] . Other diffraction peaks of bentonite observe at 2θ=19.9 ° , 26.6 ° , 28.58 ° , 36.0 ° , 42.5 ° and 61.7 ° [103–106] .…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The intensity of this peak decreased in all three samples and almost vanished in 30 % Fe(III)/bent. It showed that crystallinity of SiO 2 turned to amorphous nature [88,96,102] as similar observation made by us in our previous work [93,94] . Other diffraction peaks of bentonite observe at 2θ=19.9 ° , 26.6 ° , 28.58 ° , 36.0 ° , 42.5 ° and 61.7 ° [103–106] .…”
Section: Resultssupporting
confidence: 86%
“…The low intensity peak at 61.7 ° reveals about octahedral sheet in bentonite [105] which remains intact in all three samples. It indicates that no distraction occurred in octahedral sheet after supporting of Fe(III) while in our reported work, this peak almost disappeared as percentage TSA & TPA increased in bentonite which could led to some distraction in octahedral sheet [93,94] . A new peaks 30.81 ° , 38.67 ° , 44.54 ° , 67.07 ° , 67.47 ° and 80.53 can be assigned to Fe(III) over bentonite and some peaks such as 38.67 ° , 67.07 ° , 67.47 ° and 80.53 ° are not detected at higher loading (20 & 30 % Fe(III)/bent).…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…and its effectiveness as an catalyst has been explored in various organic transformations. [30][31][32][33] Therefore, we synthesized Keggin type quaternary vanadomolybdotungstophosphoric heteropoly acid H 5 PW 6 Mo 4 V 2 O 40 .14H 2 O (abbreviated as VMWP). It looks that the substitution of vanadium into the Keggin framework increasing the thermal stability and catalysis ability also increases.…”
Section: Introductionmentioning
confidence: 99%